2023
DOI: 10.22271/j.ento.2023.v11.i3a.9195
|View full text |Cite
|
Sign up to set email alerts
|

Determination of species composition and effective of plant extracts to prevent the eggs-lay of fruit flies, Bactrocera spp. infesting jackfruit

Abstract: Determining the composition of fruit flies damage to jackfruit and effect of some plant extracts to prevent fruit fly egg laying was carried out from January to November 2022 at Southern Horticultural Research Institute (SOFRI) and the jackfruit farms at Tan Lap and Tan Thanh communes, Tan Thanh district, Long An province. The results of determining the composition of "Changai" jackfruit fruit fly species in 15 orchards revealed that there were two fruit fly species, Bactrocera dorsalis and B. umbrosa with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gymnanthemum amygdalinum extracts have inhibitory activity on tested bacteria (Klebsiella pneumonia, Salmonella enterica, Klebsiella pneumonia and Streptococcus aureus) [7] . Hanh and Hang [8] demonstrated that extracts of A. indica (neem seeds), W. trilobata (Wedelia), Allium cepa (onion), Artemisia absinthium (mugwort) and Allium sativum (garlic) effectively prevented the laying of fruit flies at 82.22%, 71.50%, 67.86%, 63.28% and 42.82% respectively. Gymnanthemum amygdalinum has various bioactivities with little or no side effects [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Gymnanthemum amygdalinum extracts have inhibitory activity on tested bacteria (Klebsiella pneumonia, Salmonella enterica, Klebsiella pneumonia and Streptococcus aureus) [7] . Hanh and Hang [8] demonstrated that extracts of A. indica (neem seeds), W. trilobata (Wedelia), Allium cepa (onion), Artemisia absinthium (mugwort) and Allium sativum (garlic) effectively prevented the laying of fruit flies at 82.22%, 71.50%, 67.86%, 63.28% and 42.82% respectively. Gymnanthemum amygdalinum has various bioactivities with little or no side effects [9] .…”
Section: Introductionmentioning
confidence: 99%